Talking Past Each Other: Politics of Knowledge Production in Transnational Power Relations - Nader Talebi (Nordic Journal of Migration Research)
This article is an autoethnographic reflection on the complexities of transnational power relations involved in knowledge production on migration. It is based on the author’s experiences in German academia between 2015 and 2022 as a first-generation migrant from the Middle East. The article engages with the complexity of transnational spaces and the consequences of this complexity for conceptualisation, categorisation and problematisation in migration studies. Tracing such complexities is followed by a discussion on colonial legacies in academic discourses in Germany, on the one hand, and oppressive regimes’ appropriation of anti-colonial efforts in the Middle East, on the other. By drawing on examples from teaching, research and public discussions, the article demarcates a ‘reorientalist’ tendency in migration studies, which renders Middle Eastern people mere victims of colonial intervention, casting them as passive subaltern subjects, and reproducing a Eurocentric gaze with a decolonial façade. Lastly, it discusses the researchers’ multiple and shifting positionalities from the viewpoint of a migrant researcher conducting research on migration. The article calls for consistent mapping of studies through inclusive partnerships spanning diverse geographies to explore multifaceted perspectives.